2011
DOI: 10.1002/asia.201000826
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic versus Iron‐Assisted β‐Boration of Electron‐Deficient Olefins

Abstract: In the light of current debates surrounding sustainable and green chemistry, iron has now become an attractive alternative to the most commonly used expensive noble metals in a number of homogenous catalytic reactions, as it is abundant, inexpensive, less toxic, and environmentally more acceptable. [1] Despite the intense interest in the homogenous catalytic applications of iron complexes, the only known examples of iron-mediated C À B bond formation are the 1,4-hydroboration of 1,3-dienes to obtain linear (E)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…The same team of authors also showed that iron(II) salts serve as Lewis acids in the (racemic) organocatalysed conjugate borylation. 90…”
Section: Note Added In Proofmentioning
confidence: 99%
“…The same team of authors also showed that iron(II) salts serve as Lewis acids in the (racemic) organocatalysed conjugate borylation. 90…”
Section: Note Added In Proofmentioning
confidence: 99%
“…Assuming the organocatalytic variant proceeded through this sort of mechanism, Fernández et al examined the influence of Lewis acidic iron salt additives, as a means of activating 71 the Michael acceptor towards conjugate addition. 51 Scheme 15 Mechanism for the copper catalysed β-boration of α,β-unsaturated species as supported by Marder et al's DFT calculations. 69 Scheme 16 Spectroscopic evidence for the proposed organocatalytic route as described by Fernández et al 48 This journal is © The Royal Society of Chemistry 2012…”
Section: Enantioselective β-Boration: Ketones and Iminesmentioning
confidence: 93%
“…Building on their previous work, Fernández and Gulyás et al explored their newly devised non-metal catalysed route to the β-boration of α,β-unsaturated species, and examined the role of iron as an additive as a means of assisting this process. 51 This case will be discussed later (section 1.5), as it provides mechanistic insight to the process of boron conjugate addition.…”
Section: ð4þ ð5þmentioning
confidence: 99%
“…To our delight, most substituted alkyl bromides were well tolerated under the optimized conditions, leading to the desired products in moderate to good yields. Many substituents could be tolerated, including fluoro, bromo, carboxylic, and acetic groups (entries [1][2][3][4][5][6][7][8]. Similarly, the boronic acid group of 4-vinylphenylboronic acid was fine in the transformation (entry 9).…”
Section: Introductionmentioning
confidence: 98%